2007
DOI: 10.1158/0008-5472.can-06-4582
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α Mediates Breast Cancer Cell Resistance to Paclitaxel through Inhibition of Apoptotic Cell Death

Abstract: Estrogen receptors (ER) are expressed in f65% of human breast cancer. Cumulative data from clinical trials and retrospective analyses suggest that some chemotherapeutic agents may be less effective in patients with ER-positive (ER+) tumors than those with ER-negative (ERÀ) tumors. Paclitaxel is an active agent used in breast cancer chemotherapy. To investigate the possible influence of ER on the therapeutic efficacy of paclitaxel and its underlying mechanism, we established several isogenic ER+ cell lines by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 38 publications
6
100
0
Order By: Relevance
“…(Anand et al 2003, Yang et al 2006. Also known is that estrogen protects breast and ovarian cancer cells from taxol-induced apoptosis (Mabuchi et al 2004, Sui et al 2007. Based on our data that Aurora-A downregulation can override E 2 -induced growth and transformation, we speculated that downregulation of Aurora-A might counteract the estrogen-mediated decrease in Doc sensitivity as well.…”
Section: Aurora-a Knockdown Overrides Estrogenmediated Decrease In Domentioning
confidence: 82%
See 1 more Smart Citation
“…(Anand et al 2003, Yang et al 2006. Also known is that estrogen protects breast and ovarian cancer cells from taxol-induced apoptosis (Mabuchi et al 2004, Sui et al 2007. Based on our data that Aurora-A downregulation can override E 2 -induced growth and transformation, we speculated that downregulation of Aurora-A might counteract the estrogen-mediated decrease in Doc sensitivity as well.…”
Section: Aurora-a Knockdown Overrides Estrogenmediated Decrease In Domentioning
confidence: 82%
“…Alternatively, in addition to being pro-proliferative, estrogen has been shown to be a survival factor also. Estrogen has been shown to abrogate the apoptotic response of ovarian cancer cells to paclitaxel (Mabuchi et al 2004) and ER-positive breast cancer cells tend to be more resistant to anti-neoplastic drugs such as paclitaxel and Doc (Sui et al 2007). On the other hand, Aurora-A has been emerging as on anti-cancer target for reasons related to its role in cell cycle regulation, checkpoint evasion, centrosome amplification, and aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these highly characterized mutations, epigenetic alterations resulting in aberrant gene expression are key contributor to breast tumorigenesis (Campan et al, 2006;Giacinti et al, 2006;Mirza et al, 2007;Sharma et al, 2005;Sui et al, 2007;VincentSalomon et al, 2007;Visvanathan et al, 2006;Zhou et al, 2006. Decreased methylation of repetitive sequences in the satellite DNA of the pericentric region of chromosomes is associated with increased chromosomal rearrangements, mitotic recombination, and aneuploidy (Eden et al, 2003,Karpf andMatsui, 2005).…”
Section: Dna Methylation and Breast Cancermentioning
confidence: 99%
“…Neoadjuvant chemotherapy has a well-established role in the management of early-stage, operable breast cancer, and remains the gold standard downstaging systemic therapy in many centers, regardless of ER status. However, the data from other clinical trials or retrospective analyses suggest that ER status might also affect the efficacy of chemotherapy (5)(6)(7)(8). Specifically, it has been observed that some chemotherapeutic agents may be less effective in patients with ER+ tumors than those with ER-tumors.…”
Section: Role Of Estrogen and Estrogen Receptors In Chemoresistance 507mentioning
confidence: 99%
“…More recently, in a retrospective clinical study conducted by us and our collaborators, we found that primary breast cancer patienhts with ER+ tumors achieved significant lower pathologic response than those with ER-breast tumors when treated with preoperative chemotherapeutic regimens including DEC (docetaxel+epirubicin+cyclophosphamide), VFC (vinorelbine/vincristine+5-fluorouracil+ cyclophosphamide) and EFC (epirubicin+5-fluorouracil+cyclophosphamide) (34). The involvement of ER in chemoresistance has also been confirmed in a number of in vitro studies (5,7,8,(35)(36)(37)(38)(39)(40). For example, ER-breast cancer tissue was found chemosensitive in vitro compared with ER+ tissue against six antitumor drugs including carboquone, adriamycin, mitomycin C, aclacinomycin A, cisplatin and 5-fluorouracil (5).…”
Section: Current Understnding Of Er-mediated Chemoresistancementioning
confidence: 99%